2017
DOI: 10.1108/ijaim-05-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

The role of audit quality and culture influence on earnings management in companies with excessive free cash flow

Abstract: Purpose The purpose of this paper is to examine the effect of culture and audit quality on managers’ decisions regarding accounting accruals. It focuses on companies experiencing excessive free cash flow, as these companies have been associated with an agency problem. Design/methodology/approach This study measures the magnitude of discretionary accruals as a proxy for earnings management using the cross-sectional modified Jones model. Excessive free cash flow is scrutinized by the method used by Chung et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 59 publications
(75 reference statements)
2
27
0
4
Order By: Relevance
“…Furthermore Lennox et al (2016) says that a measure, accrual accounting, is the main indicator of earnings quality. Astami et al (2017) described the differences in the company's accounting earnings and the underlying cash flow. Large positive accruals indicate that earnings are higher than the cash flow obtained by the company.…”
Section: Earning Persistence Reputation and Company Valuementioning
confidence: 99%
“…Furthermore Lennox et al (2016) says that a measure, accrual accounting, is the main indicator of earnings quality. Astami et al (2017) described the differences in the company's accounting earnings and the underlying cash flow. Large positive accruals indicate that earnings are higher than the cash flow obtained by the company.…”
Section: Earning Persistence Reputation and Company Valuementioning
confidence: 99%
“…Many studies documented the benefit of using a combination of structured and unstructured data in audit evidence (Janvrin & Weidenmier Watson, 2017;Astami et al, 2017). Tang and Karim (2019) found that an auditor's use of unstructured data is still limited and thus recommended upgrading the practitioners' skills to manage the data variety, velocity, volume, veracity, and value.…”
Section: Emerging Technologies In Auditing and Assurancementioning
confidence: 99%
“…The authors declare that earnings management increases when accounting data directly affect the magnitude of tariffs imposed on the trade investigation and decreases with the increasing number of petitioning enterprises. Astami et al (2017) investigate the role of culture and audit quality on managerial decisions regarding accounting accruals using the cross-sectional modified Jones model. The interrelationships between national culture and accounting practices were revealed also in the research of Paredes and Wheatley, (2017) and Ferramosca and Allegrini (2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%